Buenos y malos extranjeros: la formación de clases como perspectiva ante las admisiones y exclusiones en la política migratoria de Estados Unidos en el siglo XX - Alfaro-Velcamp, Theresa (El Colegio de México, A.C., 2014)
This article focuses on the admission or exclusion of immigrants in the U.S., and documents the concept of the immigrants as eligible for admission only if they embody good moral character which extends in practice to being healthy, and not a burden by disease or for lacking sufficient economic resources to join the body politic. This article also describes the emergence of refugee policy as a reflection of how the U.S. government values the political beliefs of individuals and thus establishes selective criteria for admission, social welfare, and citizenship of refugees as “good foreigners.” Together, these aspects of U.S. immigration policy illustrate how immigration relates to class formation, that is, how the use of categories of exclusion and inclusion structure the “productive relationships” between people, and select who those people are.